The 19 Genomes of Drosophila: A BAC Library Resource for Genus-Wide and Genome-Scale Comparative Evolutionary Research - Song, Xiang; Goicoechea, Jose Luis; Ammiraju, Jetty S S; Luo, Meizhong; He, Ruifeng; Lin, Jinke; Lee, So-Jeong; Sisneros, Nicholas; Watts, Tom; Kudrna, David A; Golser, Wolfgang; Ashley, Elizabeth; et al. (Genetics (Austin), 2011)
The genus Drosophila has been the subject of intense comparative phylogenomics characterization to provide insights into genome evolution under diverse biological and ecological contexts and to functionally annotate the Drosophila melanogaster genome, a model system for animal and insect genetics. Recent sequencing of 11 additional Drosophila species from various divergence points of the genus is a first step in this direction. However, to fully reap the benefits of this resource, the Drosophila community is faced with two critical needs: i.e., the expansion of genomic resources from a much broader range of phylogenetic diversity and the development of additional resources to aid in finishing the existing draft genomes. To address these needs, we report the first synthesis of a comprehensive set of bacterial artificial chromosome (BAC) resources for 19 Drosophila species from all three subgenera. Ten libraries were derived from the exact source used to generate 10 of the 12 draft genomes, while the rest were generated from a strategically selected set of species on the basis of salient ecological and life history features and their phylogenetic positions. The majority of the new species have at least one sequenced reference genome for immediate comparative benefit. This 19-BAC library set was rigorously characterized and shown to have large insert sizes (125–168 kb), low nonrecombinant clone content (0.3–5.3%), and deep coverage (9.1–42.9×). Further, we demonstrated the utility of this BAC resource for generating physical maps of targeted loci, refining draft sequence assemblies and identifying potential genomic rearrangements across the phylogeny.